New Syllabus Primary Mathematics, Supplementary Reading Material - DR Foong pui Yee (Oxford University Press, 2019)
The **New Syllabus Primary Mathematics Workbook 2A, 2nd Edition** is designed to support young learners in reinforcing and applying their mathematical knowledge through engaging activities. This workbook offers a range of exercises that align with the progressive learning approach of the NSPM series, providing students with opportunities to practice and solidify their understanding of key concepts. Features include clear instructions, interactive problems, and a variety of activities that cover essential mathematical topics in a child-friendly manner. The workbook supports the Concrete-Pictorial-Abstract method and includes sections for immediate practice, self-assessment, and reflection to enhance students' learning experience and track their progress effectively.
Keywords: Textbook Maths -- Workbook